2013
DOI: 10.3389/fpls.2013.00352
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Arabidopsis root development by small signaling peptides

Abstract: Plant root systems arise de novo from a single embryonic root. Complex and highly coordinated developmental networks are required to ensure the formation of lateral organs maximizes plant fitness. The Arabidopsis root is well-suited to dissection of regulatory and developmental networks due to its highly ordered, predictable structure. A myriad of regulatory signaling networks control the development of plant roots, from the classical hormones such as auxin and cytokinin to short-range positional signaling mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 51 publications
(70 reference statements)
2
32
1
Order By: Relevance
“…3). Previous studies connecting nutrient acquisition and SSP function in M. truncatula have focused largely on the roles of CLE and CEP genes in N status-dependent root development and nodulation (Mortier et al, 2010;Delay et al, 2013a;Imin et al, 2013;Okamoto et al, 2013;Araya et al, 2014;Huault et al, 2014;Tabata et al, 2014;Mohd-Radzman et al, 2016;Ohkubo et al, 2017). Demonstrating the validity of our data sets, we could confirm these previous reports of CLE and CEP regulation (Supplemental Table S7).…”
Section: Hundreds Of Ssps Are Regulated During Nodulation and By Macrsupporting
confidence: 81%
“…3). Previous studies connecting nutrient acquisition and SSP function in M. truncatula have focused largely on the roles of CLE and CEP genes in N status-dependent root development and nodulation (Mortier et al, 2010;Delay et al, 2013a;Imin et al, 2013;Okamoto et al, 2013;Araya et al, 2014;Huault et al, 2014;Tabata et al, 2014;Mohd-Radzman et al, 2016;Ohkubo et al, 2017). Demonstrating the validity of our data sets, we could confirm these previous reports of CLE and CEP regulation (Supplemental Table S7).…”
Section: Hundreds Of Ssps Are Regulated During Nodulation and By Macrsupporting
confidence: 81%
“…To balance the carbon cost to the host with the benefits of N‐fixation, nodule number and activity is carefully regulated by systemic mechanisms that involve the long‐distance root‐to‐shoot movement of peptide hormones. Specific members of the CLE peptide family negatively regulate nodule number by a process called autoregulation of nodulation (AON) (Ferguson et al ., ; Mortier et al ., ; Reid et al ., ; Suzaki et al ., ; Djordjevic et al ., ; Shabala et al ., ; Kassaw et al ., ) and C ‐TERMINALLY ENCODED PEPTIDE (CEP) family members positively control nodule number (Delay et al ., ; Imin et al ., ; Mohd‐Radzman et al ., , ). In CLE‐dependent AON, the descending shoot‐derived AON signal and the mechanism by which it restricts nodulation have not been conclusively identified.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported that GLV/RGF/CLE-like peptides interplay with auxin to regulate root gravitropism by regulating auxin transport (66,67). Another report showed that ARF7-mediated induction of peptide gene IDA by auxin is involved in the regulation of lateral root initiation (67,68).…”
Section: Discussionmentioning
confidence: 99%
“…Another report showed that ARF7-mediated induction of peptide gene IDA by auxin is involved in the regulation of lateral root initiation (67,68). However, the molecular mechanism underlying auxin-induced IDA expression is unknown.…”
Section: Discussionmentioning
confidence: 99%